Rancang Ontology Untuk Sistem Pencarian Produk Smartwatch Berbasis Web Sematic - Suryaningsih, Ni Luh Eka Eka (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 2 No 2 (2024): JNATIA Vol. 2, No. 2, Februari 2024, 2024)
The increasing popularity of smartwatches in the digital era has highlighted the need for efficient and relevant search systems to assist users in selecting the right product. Semantic Web technology, specifically ontology-based approaches, offer a promising solution for optimizing smartwatch product searches. This research aims to design an ontology for a Semantic Web-based smartwatch product search system using the Methontology methodology. The designed ontology enables users to search for smartwatches based on preferences such as brand, price, features, and specifications. The ontology facilitates the development of a recommendation system for personalized smartwatch suggestions. The evaluation of the ontology through SPARQL queries demonstrates its effectiveness in representing smartwatch product information. This research contributes to enhancing user experiences and decision-making processes when purchasing smartwatches.